Am Rande der Fotografie Eine Medialitätsgeschichte des Fotogramms im 19. Jahrhundert - Steidl, Katharina (De Gruyter, 2018)
Why is there a history of photography but no history of the photogram? The publication pursues this question by approaching the specific materiality, the scientific and artistic qualities of the photogram on the basis of a historiographic, semiotic and gender-theoretical analysis. Thereby a still outstanding media history of the photogram is realized and the historical relevance of this so far neglected medium is worked out.